2021
DOI: 10.1097/mao.0000000000003172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cochlear Implantation on Tinnitus and Quality of Life: A Systematic Review and Meta-analysis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
(248 reference statements)
0
14
0
Order By: Relevance
“…Cochlear implantation improves general hearing abilities, speech perception, and sound localization in patients with asymmetric hearing loss (AHL) ( 2 ), single-sided (unilateral) deafness (SSD) ( 3 ), and double-sided (bilateral) deafness (DSD) ( 4 ). Accumulating evidence suggests that the beneficial effects of implantation extend beyond the main indication (improvement of auditory abilities) and can positively impact cognition ( 5 7 ), health-related quality of life ( 6 , 8 ), and comorbid symptoms such as depression or anxiety ( 9 ). Additionally, the predominantly positive influence of implantation on tinnitus presence and tinnitus-induced distress is well-documented ( 9 , 10 ), although the exact mechanism of this phenomenon is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochlear implantation improves general hearing abilities, speech perception, and sound localization in patients with asymmetric hearing loss (AHL) ( 2 ), single-sided (unilateral) deafness (SSD) ( 3 ), and double-sided (bilateral) deafness (DSD) ( 4 ). Accumulating evidence suggests that the beneficial effects of implantation extend beyond the main indication (improvement of auditory abilities) and can positively impact cognition ( 5 7 ), health-related quality of life ( 6 , 8 ), and comorbid symptoms such as depression or anxiety ( 9 ). Additionally, the predominantly positive influence of implantation on tinnitus presence and tinnitus-induced distress is well-documented ( 9 , 10 ), although the exact mechanism of this phenomenon is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that the beneficial effects of implantation extend beyond the main indication (improvement of auditory abilities) and can positively impact cognition ( 5 7 ), health-related quality of life ( 6 , 8 ), and comorbid symptoms such as depression or anxiety ( 9 ). Additionally, the predominantly positive influence of implantation on tinnitus presence and tinnitus-induced distress is well-documented ( 9 , 10 ), although the exact mechanism of this phenomenon is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing aid referral 1,78,[208][209][210][211] or cochlear implant [212][213][214][215][216][217] Mitigating hearing loss with hearing aids can decrease the perception of tinnitus. Tinnitus retraining therapy 218 A multimodal habituation-based treatment; tinnitus-specific educational counseling and sound therapy.…”
Section: Hearing Habilitation and Audiology Servicesmentioning
confidence: 99%
“…CIs can restore hearing by directly stimulating the auditory nerve electrically. Several studies and reviews have concluded that CI use improves the speech perception ability and health-related quality of life (HRQOL) of people with SNHL [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%